Experience in Oral Cancer Reconstruction in a Tertiary Care Center of Nepal - Pradhan, Rohan; Rayamajhi, Sangam; Sharma, Samit; Rai, Sushant; Rajbhandari, Bikesh; Niraula, Himalaya; Shrestha, Jayan M; Lohani, Ishwor (Journal of Institute of Medicine Nepal, 2022)
Introduction: Oral cancer is one of the most common malignancies in Nepal. Most patients have locally advanced disease during their initial presentation, necessitating substantial resection and leaving significant deformity. Functional and anatomical restoration of these defects is crucial. This study analyzed the clinical presentation of oral cancer, surgical management, and encountered complications in the Nepalese context. Methods: This was a single-center retrospective study of oral cancer reconstruction performed at Tribhuvan University Teaching Hospital, Kathmandu over four years period (September 2018 - September 2022). Demographics, clinical presentation, comorbidities, treatment, and complications were recorded and analyzed. Results: Out of the analysis of 36 cases of oral cancer, most of the patients were in the fifth decade of life with male to female ratio of 3:1. The most common primary site involved was buccal mucosa (38.88%). Twenty-two cases (61.11%) were in the locally advanced stage. Tobacco chewing was a common entity in personal habits. Surgery consisted of eighteen pedicled, sixteen free flaps, and five local flaps. Pectoralis major myocutaneous flap was the commonest flap performed (38.46%). The overall complication rate was 58.33%. Orocutaneous fistula was the commonest (22.22%). The partial flap loss occurred in 8.33% (15.1%) and the total flap loss occurred in three free flaps. Conclusion: The difficulties experienced in OC reconstruction were high complication rates, multiple redo surgeries, and extended hospital stays. Despite these challenges, all of our patients were released from the hospital with stable wound coverage. Furthermore, the study will provide a platform for a better understanding of the oral cancer reconstruction scenario in the context of Nepal.